PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN - Suryani, Dewita; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine how the Effect of Parenting Parents on Emotional Social Development of Children Aged 5-6 Years in Assalam Kindergarten, West Pontianak. The research method used is descriptive quantitative research. The data source of this research is 29 parents and 29 children of B3 group in Assalam Kindergarten, West Pontianak. This research technique is by observation with an observation sheet, the use of questionnaires with questionnaires, and documentaries with documentation tools. Analysis of the data in this study is simple linear regression. Based on the results of research that has been done and through the results obtained from data analysis, in general it can be concluded that the results of the study indicate the value of parenting parents on children's social emotional development of 3,463 with Sig. (2-tailed) of 0,000, so compared to the significance level of 0.05 (5%), the Sig. (2-tailed) is smaller than 0.05 (5%). This means that there is an influence of parenting variable (X) on the emotional social development of children (Y) aged 5-6 years in TK Assalam, West Pontianak. Then, the value of the coefficient of determination (R Square) is also known at 0.114. This means increasingly proving that the influence of parenting parents on children's social emotional development is 11.4% and only 0.17% is influenced by other factors.Â Keywords:Parenting, Emotional Social Development AUD